Integrating new sea‐level scenarios into coastal risk and adaptation assessments: An ongoing process. (22nd March 2021) - Nicholls, Robert J.; Hanson, Susan E.; Lowe, Jason A.; Slangen, Aimée B. A.; Wahl, Thomas; Hinkel, Jochen; Long, Antony J.
Abstract: The release of new and updated sea‐level rise (SLR) information, such as from the Intergovernmental Panel on Climate Change (IPCC) Assessment Reports, needs to be better anticipated in coastal risk and adaptation assessments. This requires risk and adaptation assessments to be regularly reviewed and updated as needed, reflecting the new information but retaining useful information from earlier assessments. In this paper, updated guidance on the types of SLR information available is presented, including for sea‐level extremes. An intercomparison of the evolution of the headline projected ranges across all the IPCC reports show an increase from the fourth and fifth assessments to the most recent " Special Report on the Ocean and Cryosphere in a Changing Climate " assessment. IPCC reports have begun to highlight the importance of potential high‐end sea‐level response, mainly reflecting uncertainties in the Greenland/Antarctic ice sheet components, and how this might be considered in scenarios. The methods that are developed here are practical and consider coastal risk assessment, adaptation planning, and long‐term decision‐making to be an ongoing process and ensure that despite the large uncertainties, pragmatic adaptation decisions can be made. It is concluded that new sea‐level information should not be seen as an automatic reason for abandoning existing assessments, but as an opportunity to review (i) the assessment's robustness in the light of new science and (ii) the utility of proactive adaptation and planning strategies, especially over the more uncertain longer term. This article is categorized under: Assessing Impacts of Climate Change > Scenario Development and Application Abstract : Evolving IPCC global mean sea‐level scenarios, improving understanding of risk, and increasing use of adaptation—the release of new scenarios triggers re‐evaluation of existing risk and adaptation assessments with new knowledge rather than automatic replacement.